The Imperative of Revising the Arbitration Exception in the Brussels I bis Regulation - Tičić, Martina (LeXonomica, 2025)
Arbitration represents a popular alternative dispute resolution mechanism in the European Union (EU). However, the coexistence of arbitration and court litigation in the EU legal area has been proven to be quite difficult to regulate. At the EU level, the Brussels I bis Regulation, i.e., the main instrument governing jurisdiction and recognition and enforcement of judgments in civil and commercial matters, explicitly states that arbitration does not fall under its scope. This ‘arbitration exception’ has led to difficulties in practice, many of which have found their way to the Court of Justice of the EU (CJEU). However, as the CJEU case law shows, it only led to new questions. As these issues will keep emerging, a different solution must be found. The perfect moment for such change is now, as the reform of the Brussels I bis Regulation is ongoing. This paper thus presents the intricacies of the ‘thorny’ interplay of arbitration and court litigation in the EU. In order to remedy the existing problems in practice, two potential solutions are suggested.Povzetek članka v slovenskem jeziku (abstract in Slovene language):Arbitraža je v Evropski uniji (EU) priljubljen mehanizem alternativnega reševanja sporov. Vendar se je izkazalo, da je soobstoj arbitraže in sodnih postopkov na pravnem področju EU precej težko urediti. Na ravni EU je v uredbi Bruselj I bis, tj. glavnem instrumentu, ki ureja pristojnost ter priznavanje in izvrševanje sodnih odločb v civilnih in gospodarskih zadevah, izrecno navedeno, da arbitraža ne spada na njeno področje uporabe. Zaradi te „arbitražne izjeme“ so se v praksi pojavile težave, od katerih jih je veliko prišlo do Sodišča EU (SEU). Vendar je, kot kaže sodna praksa Sodišča EU, privedla le do novih vprašanj. Ker se bodo ta vprašanja še naprej pojavljala, je treba najti drugačno rešitev. Idealen trenutek za takšno spremembo je zdaj, ko poteka reforma uredbe Bruselj I bis. V tem prispevku so tako predstavljene zapletene podrobnosti „kočljivega“ prepletanja arbitraže in sodnih postopkov v EU. Za odpravo obstoječih težav v praksi sta predlagani dve možni rešitvi.